Differences in the functional use of two migratory stopovers by humpback whales (Megaptera novaeangliae). - Raphael Mayaud; Joshua N Smith; David Peel; Craig Wilson; Wally Franklin; Tim Stevens; Susan Bengtson Nash (PLoS ONE)
Humpback whale migration between tropical breeding grounds and polar feeding grounds is an energy-intensive activity undertaken on finite energy stores. The use of stopover sites to rest reduces energetic expenditure and provides enhanced opportunity for calves to nurse during migration. Moreton Bay is a newly identified migratory stopover for Australia's east coast humpback whale population. Understanding the functional roles of stopovers is essential for a holistic understanding of population dynamics and connectivity. Therefore, contextualising the significance of Moreton Bay relative to a well-established stopover like Hervey Bay, can provide valuable insights into their functional roles within the broader migratory network, helping to inform targeted conservation efforts. To investigate this, we conducted a total of 865km of systematic, boat-based line transects across the two distinct geographical regions during temporally staggered periods (August and September - October) of the 2021 humpback whale migration. We examined population structure, behaviour, and habitat segregation, and developed spatial density surface models to predict density distribution patterns at each respective site. Our results show that Hervey Bay supports a more heterogenous mix of demographic groups, while Moreton Bay had a significantly greater number of calf-groups (z = 4.53, p = 0.017). Both bays exhibited similar resting behaviours, but social interactions among juveniles were unique to Hervey Bay. These findings suggest Moreton Bay serves a more utilitarian role as a stopover, functioning primarily as a resting site for mother-calf pairs, rather than the multifaceted use described in Hervey Bay. As lactating females and their calves are particularly vulnerable to anthropogenic threats like vessel strike, it is imperative to understand how different habitats contribute to the success of migration and ensure adequate protection is maintained.